Understanding social media for information professionals - Kamarulzaman, Rabiatul Adawiyah; Jamil, Nurul Huda Izzati; Othman, Razifah; Osman, Suhaila (Universiti Teknologi MARA, Johor, 2025)
Social media has become one of the most transformative forces in the information age, reshaping how people create, share, and consume knowledge globally. Defined as digital platforms that facilitate communication, collaboration, and user-generated content, social media enable individuals and organizations to interact dynamically within online communities (Kaplan & Haenlein, 2010; Verishagen, 2018). From Facebook and Instagram to emerging platforms such as TikTok and Threads, the social media landscape continues to expand, influencing not only social behavior but also the way information professionals engage with users.